PENGARUH RISIKO KEUANGAN DAN PERTUMBUHAN PENJUALAN PADA PROFITABILITAS DAN NILAI PERUSAHAAN PROPERTY - Alit Dramawan, I Dewa Ketut (Buletin Studi Ekonomi; VOL.20.NO.2.AGUSTUS 2015 (PP 83-176), 2016)
The Effect of Financial Risk and Sales Growth to Profitability and Value of The Firm. This research is conducted as a mean to determine the effect of financial risk and sales growth to profitability and value of the firm. The study population is a property company that is listed on the Indonesia Stock Exchange 2010-2012. The sample is based on the census in accordance with the definition of the variables used in this research, 26 companies as samples. Variables financial risk is measured by delta EPS divided by delta EBIT, sales growth is measured by the proportion of delta sales each year, profitability with ROA ( return on assets), value of the firm with PBV ( price to book value ). Analysis of the data using path analysis method , in which the financial risk and sales growth as an exogenous variable, value of the firm as an  endogenous variable and profitability as an intervening variable. The research found that the risk of finance and sales growth have positive effect on pofitability, profitability has positive effect on the value of the firm but financial risk value and growth sales have negative effect on the value of the firm.   Keywords : financial risk, sales growth, profitability, value of the firm
Keywords: financial risk, sales growth, profitability, value of the firm